Treatment of Midshaft Clavicular Fractures With Elastic Titanium Nails - Keihan Shokouh, Hassan (Kowsar, 2014)
BACKGROUND: One of the modern techniques for the treatment of clavicle fracture (Fx) is elastic titanium intramedullary nailing. But, there are different opinions about this technique. We studied this technique in 12 patients with clavicle Fx and assessed its outcome. OBJECTIVES: We aimed to study the prognosis of midshaft clavicular Fx treated via minimally invasive stable elastic intramedullary nailing. PATIENTS AND METHODS: We operated on 13 clavicle Fx in 12 patients from 2008 through 2012. We used a new technique called minimally invasive titanium elastic intramedullary nailing for operating patients with midshaft clavicular Fx. RESULTS: Clinical union was achieved 3-5 weeks after the operation with no pain over Fx sites upon physical examination. Radiologic union appeared at 6 to 12 weeks .We did not encounter nonunion or infection, but one of the comminuted Fx united 1 cm shorter; however, it had a solid union with a good score. All but two patients had good scores. CONCLUSIONS: Although controversy exist regarding intramedullary nailing of clavicle Fx, our results using this technique for minimally comminuted midshaft clavicular Fx were very good.